An Analysis of the implications of forage legumes and a cereal-based cropping system for sustainable agriculture in Ethiopia: A linear programming approach - Kassie, M.; Jabbar, M.A.; Kassa, B. (1998)
One of the factors that constrains animal draft power in livestock-rich countries like Ethiopia is the inadequate supply of livestock feed both in quantitative and qualitative terms. This problem in Ethiopia is aggravated by poor soil conditions across the highland areas. Inter-cropping of forage legumes with cereal crops can restore soil fertility, reduce the need for imported inputs, alleviate the problem of shortfalls in the quality and quantity supply of livestock feed, and enhance the draft power efficiency of oxen. Nitrogen (N) input from forage legumes can help maintain the soil N reserve as well as substituting for inorganic fertilisers to attain large crop yields. Using a linear programming model, this article examines the economic impacts of the inter-cropping system that combines forage and food crop cultivation, based on resources available to farmers and on prevailing agricultural practices in the Ethiopian highlands.